Pharyngeal residue in the neurogenic oropharyngeal dysphagia - de Souza, Giovana Aparecida Dias [UNESP]; da Silva, Roberta Gonçalves [UNESP]; Cola, Paula Cristina [UNESP]; Onofri, Suely Mayumi Motonaga [UNESP] (FapUNIFESP (SciELO), 2019)
Purpose: To compare pharyngeal residues of different consistencies among groups of individuals with neurogenic oropharyngeal dysphagia. Methods: In a cross-sectional study, a fiberoptic endoscopic evaluation was performed in 30 swallowing exams of individuals diagnosed with neurological disease and oropharyngeal dysphagia, regardless of the time or stage of the disease. The individuals were divided into three groups according to etiology: group I, 10 post-stroke, 8 male and 2 female, aged 51 to 80 years (average age: 67 years); group II, 10 individuals with amyotrophic lateral sclerosis, 5 male and 5 female, aged 39 to 78 years (average age: 57 years); group III, 10 examinations of individuals with Parkinson's disease, 5 male and 5 female aged 65-88 years (average age: 74 years). The Yale Pharyngeal Residue Severity Rating Scale was applied by two independent raters in a blind manner for the analysis of pharyngeal residues in valleculae and pyriform sinuses based on the first swallowing of 5 mL of pureed and thickened liquid. Results: No statistically significant difference was observed among groups in the degree of pharyngeal residues of puree food or thickened liquid in the valleculae (p = 0.25/p = 0.18) or the pyriform sinuses (p = 1.41/0.49). Conclusion: The pharyngeal residue levels of pureed and thickened liquid were similar for the groups studied, with less severe levels being more frequent.
Resíduos faríngeos nas disfagias orofaríngeas neurogênicas
Keywords: Amyotrophic Lateral Sclerosis; Endoscopy; Parkinson's Disease; Stroke; Swallowing Disorders